Multi-scale variability of the Asian monsoon recorded in an annually-banded stalagmite during the Neoglacial from Qixing Cave, Southwestern China. (10th September 2018) - Zhang, Zhen-Qiu; Wang, Yong-Jin; Liu, Dian-Bing; Cheng, Hai; Huang, Wei; Wang, Quan; Liang, Yi-Jia
Abstract: Solar forcing of the Asian summer monsoon (ASM) and the embedded feedback mechanism remain highly controversial. In this study, interannual-scale ASM variability from 3.58 to 2.28 ka BP is reconstructed based on the δ 18 O record of an annually laminated stalagmite from Qixing Cave in southwestern China. The cave δ 18 O record agrees well with a record of solar activity on the centennial scale during the whole time series. Furthermore, statistical analysis of singular spectrum and wavelet spectrum shows a significant cycle of ∼60 years, one of the solar activity cycles. The two lines of evidence have consolidated the solar impact on a centennial-decadal time scale of ASM variability. Timing and structure of the 2.8 ka event, detected in various archives at a global scale, have been well determined in our δ 18 O record with a high-precision time scale established by absolute 230 Th dating and annual-layer counting. We observed an asymmetrical pattern of the event, i.e. a gradual transition at the onset with a rapid end, which can be interpreted as a far-field effect of changing thermohaline circulations in the North Atlantic. We further demonstrate a striking inverse correlation between the ASM and the Indonesian–Australian summer monsoon (IASM) on the centennial scale, including three dominant ASM depression events that are related to periods of weak solar activity. The evidence we present here supports that ocean -atmosphere interactions amplified the solar signal and caused abrupt cooling events in widespread areas during the Holocene.